On the estimation of marbles weathering by thermal action using drilling resistance. (October 2021) - Sena da Fonseca, B.; Ferreira Pinto, A.P.; Rodrigues, A.; Piçarra, S.; Fonseca, D.; Montemor, M.F.
Abstract: Marbles are widely present in noteworthy constructions but are prone to decay due to the anisotropic thermal behavior of constituent minerals. In this paper, fine to coarse sound marbles possessing diverse technical properties were subjected to different artificial heating protocols to simulate varied degradation scenarios. The ultrasonic pulse velocity of sound and decayed marbles decreases exponentially with increasing porosity which is in line with the relationships found in the literature for other marble varieties. Drilling resistance (DR) revealed potential to characterize a wide diversity of marbles/degradation levels since data was in straight agreement with technical properties of interest for damage diagnosis and conservation purposes. Therefore, empirical relations based on DR results are provided to estimate technical properties of marbles on-site. Besides, this work proposes a classification, based on DR, to assess the weathering level of marbles. Highlights: Marble varieties were subjected to different artificial heating protocols. Ultrasound pulse velocity decreases exponentially with increasing porosity. Drilling resistance (DR) describe a wide diversity of marbles/degradation levels. DR results can be used to estimate other technical properties of marbles. A classification based on DR to assess the weathering level of marbles is proposed.